2015
DOI: 10.3923/ijp.2015.828.833
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Antibacterial and Antifungal Activity of Freshwater and Marine Algae as a Prominent Natural Antibiotic Available in Bangladesh

Abstract: In Bangladesh, algae have not been adequately explored for their potential as a source of bioactive substances. So, present work provides the eligibility of algae commonly found in Bangladesh as a prominent natural antibiotic against various pathogens. In vitro screening of organic solvent extracts (methanol, ethanol and chloroform) of ten fresh water and marine algae showed antimicrobial activity carried out by disc diffusion method against two gram positive, four gram negative bacteria and one fungus. Marine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
(25 reference statements)
2
5
2
Order By: Relevance
“…In this study, an ethanolic fraction of U. prolifera exhibited inhibition zones (zone range: 16–17.3 mm) on tested fungi. The results agree with the findings of Chowdhury et al [ 28 ], who reported that the growth of C. albicans was inhibited (15 mm) by an ethanolic extract of Enteromorpha prolifera . Correspondingly, the antifungal activity of U. lactuca and U. fasciata studied by Shobier et al [ 29 ] against Aspergillus flavipes and C. albicans and found activities ranging from 10 to 32 mm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, an ethanolic fraction of U. prolifera exhibited inhibition zones (zone range: 16–17.3 mm) on tested fungi. The results agree with the findings of Chowdhury et al [ 28 ], who reported that the growth of C. albicans was inhibited (15 mm) by an ethanolic extract of Enteromorpha prolifera . Correspondingly, the antifungal activity of U. lactuca and U. fasciata studied by Shobier et al [ 29 ] against Aspergillus flavipes and C. albicans and found activities ranging from 10 to 32 mm.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, organic solvents fractions obtained from U. lactuca showed no activity against C. albicans reported by Guedes et al [ 32 ]. In addition, A. spicifera had the lowest antifungal activity, in discrepancy with Pandian et al [ 33 ] and Chowdhury et al [ 28 ]. They reported that A. spicifera exhibited moderate antifungal activity against A. niger, Microsporum gypseum, and C. albicans .…”
Section: Discussioncontrasting
confidence: 68%
“…Using cyanobacteria in composts have been described as promoting resistance towards pathogens in tomato, cotton and zucchini (Dukare et al, 2011;Prasanna et al, 2013;Babu et al, 2015;Roberti et al, 2015). Different extracts of microalgal compounds have been used in interaction with pathogens to induce resistance, and is some cases how the extracts hinder growth of different pathogens directly (Jaulneau et al, 2010;Galal et al, 2011;Chowdhury et al, 2015;Stadnik and Freitas, 2014).…”
Section: Practical Application Of Cytokinin Mediated Plant Protectionmentioning
confidence: 99%
“…From Kappaphycus alvarezii , phenolic compounds, glycosides, and carbohydrates have been shown to have antibacterial effects on a variety of human pathogens [ 115 ]. Human pathogenic fungi, such as Aspergillus and Candida , showed resistance to the antifungal effects of methanolic extracts from Corallina mediterranea , Hypnea musciformis , and Laurencia papillosa [ 118 ]. A diterpene known as ‘Sphaerodactylomelol fraction 2′, recently discovered in S. coronopifolius , exhibited the most potent antifungal properties against Candida albicans [ 116 ].…”
Section: Macroalgae—a Brief Overviewmentioning
confidence: 99%